The natural history of the soul in ancient Mexico - Furst, Jill Leslie McKeever, 1944- (Yale University Press, 1995)
"Fascinating examination of Mexica thought and belief (ca. 1200-1519) regarding the soul, utilizing iconographic and ethnohistorical sources but also giving special consideration to the influence of natural environments on ideology. Cultural concepts of special note here include the Nahua yolia, ihiyotl, and tonalli. Author saves the nahualli for future study"--Handbook of Latin American Studies, v. 58.